Cobertura de la estrategia preventiva de cáncer de vesícula biliar en Chile: Resultados de la Encuesta Nacional de Salud 2009-2010 - Latorre S, Gonzalo; Ivanovic-Zuvic S, Danisa; Corsi S, Oscar; Valdivia C, Gonzalo; Margozzini M, Paula; Olea O, Ricardo; Chianale B, José; Miquel P, Juan Francisco (Revista Médica de Chile, 2015)
Background: In Chile, gallbladder cancer (GBC) is one of the most important causes of death and gallstone disease (GSD) is its main risk factor. Abdominal ultrasonography (AU) is used for the diagnosis of GSD and cholecystectomy is used to prevent it. Aim: To estimate GSD prevalence in the general population and to assess the diagnostic and therapeutic coverage of GSD as a preventive strategy for GBC in Chile. Material and Methods: A standardized digestive symptoms questionnaire of The 2009-2010 Chilean National Health Survey was answered by 5412 adults over 15 years old. Self-reports of AU, GBD and cholecystectomies were recorded. Results: The prevalence of biliary-type pain was 7.1%. During the last five years, the prevalence of AU was 16%. GSD was reported in 20% of these tests and 84% of them were asymptomatic. The prevalence of AU was significantly lower in Araucanía region and among people with less than 12 years of education. Life cholecystectomy prevalence was 11% and reached 40% in people aged over 60 years. Women accounted for 75% of total cholecystectomies. Twenty-one percent of individuals who referred biliary-type pain, were studied with an AU. Only 60% of people with GSD confirmed by AU underwent a cholecystectomy. Conclusions: GSD affects at least 27% of the Chilean adult population. Important deficits and inequities in GSD diagnostic and therapeutic coverage were identified.